2018
DOI: 10.1038/s41426-018-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular analysis of nontypeable Group B streptococci: identification of cps2a and hybrid cps2a/cps5 Group B streptococcal capsule gene clusters

Abstract: The Group B streptococcus (GBS) can express a capsular polysaccharide (CPS). There are ten recognized CPSs (Ia, Ib, and II–IX). A GBS isolate is considered nontypeable (NT) when CPS cannot be identified as one of ten types. Two groups of GBS NT isolates were studied, isolates without surface sialic acid (sia(−)) and isolates with surface sialic acid (sia(+)). The first objective was to characterize NT sia(−) isolates that failed CPS identification by an immunodiffusion antisera typing assay and a RT-PCR capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is well-known that a certain percentage of invasive GBS isolates are non-typeable (NT) by phenotypic methods, either because they do not express their capsule or the capsule is hitherto uncharacterized capsule ( Rosini et al, 2015 ; Alhhazmi and Tyrrell, 2018 ). In recent epidemiological studies NT isolates are generally found to constitute 5–10% of the invasive GBS isolates ( Lamagni et al, 2013 ; Alhhazmi et al, 2016 ; Björnsdóttir et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that a certain percentage of invasive GBS isolates are non-typeable (NT) by phenotypic methods, either because they do not express their capsule or the capsule is hitherto uncharacterized capsule ( Rosini et al, 2015 ; Alhhazmi and Tyrrell, 2018 ). In recent epidemiological studies NT isolates are generally found to constitute 5–10% of the invasive GBS isolates ( Lamagni et al, 2013 ; Alhhazmi et al, 2016 ; Björnsdóttir et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus agalactiae identification is a challenge for modern microbiological diagnostics, especially taking into account the phenotypic and molecular diversity of the strains belonging to this species [7][8][9][10]. Moreover, in recent years, an increase in GBS resistance to selected drugs has been observed [11].…”
Section: Introductionmentioning
confidence: 99%